A systematic review of economic evaluations of cardiac rehabilitation - Wong Wai; Feng Jun; Pwee Keng; Lim Jeremy (BMC, 2012)
Abstract Background Cardiac rehabilitation (CR), a multidisciplinary program consisting of exercise, risk factor modification and psychosocial intervention, forms an integral part of managing patients after myocardial infarction (MI), revascularization surgery and percutaneous coronary interventions, as well as patients with heart failure (HF). This systematic review seeks to examine the cost-effectiveness of CR for patients with MI or HF and inform policy makers in Singapore on published cost-effectiveness studies on CR. Methods Electronic databases (EMBASE, MEDLINE, NHS EED, PEDro, CINAHL) were searched from inception to May 2010 for published economic studies. Additional references were identified through searching bibliographies of included studies. Two independent reviewers selected eligible publications based on the inclusion/exclusion criteria. Quality assessment of economic evaluations was undertaken using Drummond's checklist. Results A total of 22 articles were selected for review. However five articles were further excluded because they were cost-minimization analyses, whilst one included patients with stroke. Of the final 16 articles, one article addressed both centre-based cardiac rehabilitation versus no rehabilitation, as well as home-based cardiac rehabilitation versus no rehabilitation. Therefore, nine studies compared cost-effectiveness between centre-based supervised CR and no CR; three studies examined that between centre- and home based CR; one between inpatient and outpatient CR; and four between home-based CR and no CR. These studies were characterized by differences in the study perspectives, economic study designs and time frames, as well as variability in clinical data and assumptions made on costs. Overall, the studies suggested that: (1) supervised centre-based CR was highly cost-effective and the dominant strategy when compared to no CR; (2) home-based CR was no different from centre-based CR; (3) no difference existed between inpatient and outpatient CR; and (4) home-based programs were generally cost-saving compared to no CR. Conclusions Overall, all the studies supported the implementation of CR for MI and HF. However, comparison across studies highlighted wide variability of CR program design and delivery. Policy makers need to exercise caution when generalizing these findings to the Singapore context.